Information flows of reporting on terrorism attack by online news portal - Yusoff, Sofia Hayati; Hassan, Fauziah; Md Zamin, Ainul Azmin (Human Resource Management Academic Society, 2017)
Issues related to terrorism have been reported excessively by the media in order to tell public by giving recent and significant information. Currently, online media are known to be a major source of news as they can provide information without any delayed to ensure the society stay connected with and being informed on the latest issues. Therefore, this article is specially designed to explore on how the main online news portals in Europe (http://www.euronews.com/) and Africa (http://allafrica.com/) report issues on recent attacks in Paris and Mali. The objectives in this article are threefold: to compare the coverage of news reporting; to identify the news sources used and lastly to identify the news themes that emerged in news reporting. To perform this, a qualitative content analysis approach on two different case studies have been employed and all the news samples were analysed using qualitative software namely QSR NVivo 11. The results indicated that Paris attack issues received 25 news coverage compared to Mali attack issues at 19 news coverage. In terms of news sources used, majority of the news articles used official sources such as Minister, Police officer, spokesperson, media, leader, authorities and security forces. The findings also revealed several news themes such as suspected attackers, rescue efforts, security efforts and death toll are emerged in this analysis